Laboratory parameters, clinical characteristics and hemogram-derived indices in adult patients with measles at tertiary hospital admission - Berina Hasanefendić; Amila Muratspahić; Semir Hrvo; Emina Hajrović Hebibović; Lejla Avdagić; Almedina Moro; Emir Šeherčehajić; Amir Sandžić (Medicinski glasnik, 2026)
Aim: To describe the clinical picture and laboratory findings, as well as to examine the significance of novel hemogram-derived inflammatory indices in adult patients with measles admitted to a tertiary hospital. Methods: This prospective, descriptive, and analytical study included adult patients over 18 years of age with clinical signs of measles, admitted at the Clinic for Infectious Diseases, Clinical Center of Sarajevo. Upon admission, medical history, physical examination, and laboratory analyses were conducted from February 2024 to 31 December 2024. Results: The study included 124 patients, 52 men and 72 were women with a mean age of 38.33±13.18 years. The most common symptoms in most patients were rash (95.97%) and cough (69.36%). Neutrophilia (63.7%) and lymphopenia (74.19%) were the main hematological features along with elevated C-reactive protein (CRP) (95.17%) and transaminase (75%) in the vast majority of patients. The results of laboratory analyzes also indicated hyponatremia and hypokalemia, with elevated values ​​of the enzymes creatine kinase (CK) and lactate dehydrogenase (LDH). The CRP, as the most commonly elevated laboratory parameter, showed positive, significant correlation with Neutrophil/Lymphocyte ratio (NLR), Systemic Inflammation Response Index (SIRI) (p<0.05) and Systemic immune-inflammation index (SII) and Aggregate Index of Systemic Inflammation (AISI) (p<0.01). Conclusion: Adult measles was associated with significant inflammation, hematologic changes, and organ involvement, with CRP showing strong correlations with hemogram-derived indices. These findings suggesting that they may be useful in diagnostics of measles.
Keywords: biomarkers; infectious diseases; inflammation; viremia